Restrictive versus liberal transfusion strategies for red blood cell transfusion after hip or knee surgery: A systematic review and meta-analysis - Mao, Tianli (Medicine (Baltimore), 2017)
BACKGROUND: Red blood cell (RBC) transfusions are commonly used in surgical patients, but accompanied by many risks such as metabolic derangement, and allergic and febrile reactions. Indications for transfusion in patients after hip or knee surgery have not been definitively evaluated and remain controversial. We performed a meta-analysis to compare the benefits and harms of restrictive versus liberal transfusion strategies in patients after hip or knee surgery. METHODS: The PubMed, EMBASE, and Cochrane Library databases were searched for relevant studies through September 2015. The main clinical outcomes reported in randomized controlled trials (RCTs) included 30-day mortality, infection rate, cardiogenic complications, and length of hospital stay. The meta-analysis program of the Cochrane Collaboration (RevMan version 5.3.0) was used for data analysis. Statistical heterogeneity was assessed by both Cochran chi-squared test (Q test) and I(2) test. Begg and Egger test were used to assess potential publication bias. RESULTS: We identified 10 eligible RCTs, involving 3788 patients in total. In patients undergoing hip or knee surgery, we found no differences in mortality, or the incidence rates of pneumonia, wound infection, myocardial infarction, or congestive heart failure, between restrictive and liberal thresholds for RBC transfusion (P > .05). CONCLUSION: Restrictive transfusion has no advantage over the liberal strategy. However, considerably less patients received blood transfusion via the restrictive strategy than with the liberal counterpart. Due to variations in the included studies, additional larger scale and well-designed studies are required to validate these conclusions.